PELAKSANAAN MEDIA GAMIFIKASI PADA PEMBELAJARAN SKI DI MTSN 3 SIAK KECAMATAN BUNGARAYA KABUPATEN SIAK - Nelvy Aprilianita; Fenny Ayu Monia; Hamdi Abdul Karim; Puti Andam Dewi (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2025)
Islamic Studies (SKI) learning is often perceived as monotonous by many students, requiring methods that can make the learning process more engaging and enjoyable. One solution that can be implemented is the use of gamification media, which incorporates elements from games into the learning process. The goal of applying gamification is to enhance student motivation, leading to increased participation in the lessons. At MTsN 3 Siak, the teacher of SKI for grade VIII has started to implement gamification in the learning process. This study aims to identify the planning, implementation, and challenges faced by the teacher in using gamification as a learning tool. A qualitative descriptive approach is used in this research, with the key informant being the SKI teacher, and supporting informants including students, the school principal, and the curriculum supervisor. Data was collected through observations, interviews, and documentation, and data analysis involved data collection, reduction, presentation, and conclusion drawing. Data validity was tested through triangulation techniques. The results of the study indicate that gamification media has been applied in the classroom and has proven to boost student enthusiasm and motivation during SKI lessons. However, gamification was only implemented four times within one semester, and although most students had grasped the material before engaging with the games, some students still had difficulty following the games effectively.